2015
DOI: 10.1515/prolas-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Pine (Pinus sylvestris L.) And Spruce (Picea abies (L.) Karst.) Bark Extracts On Important Strawberry Pathogens

Abstract: Phytopathogenic fungi induced considerable economic losses in strawberry production industry; therefore, more attention should be paid to development and implementation of preventative treatment that is environmentally friendly. Coniferous trees produce a wide variety of compounds, such as terpenoids and phenolics. Several studies are known on fungicidal activity of different components of coniferous tree bark. The aim of this study was to evaluatein vitropine (Pinus sylvestrisL.) and spruce (Picea abies(L.) K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Recently, Minova et al (2015) confirmed that ethanol extracts of the bark of P. abies inhibit mycelial growth of B. cinerea, C. acutatum, P. cactorum, and M. fragariae. Bark extracts can reduce the sporulation of B. cinerea, C. acutatum, and P. cactorum (Minova et al 2015). The bark extract of P. abies has the most efficient antioxidant activity within lipid peroxidation tests (Pietarinen et al 2006).…”
Section: Antifungal and Antibacterial Activitiesmentioning
confidence: 90%
“…Recently, Minova et al (2015) confirmed that ethanol extracts of the bark of P. abies inhibit mycelial growth of B. cinerea, C. acutatum, P. cactorum, and M. fragariae. Bark extracts can reduce the sporulation of B. cinerea, C. acutatum, and P. cactorum (Minova et al 2015). The bark extract of P. abies has the most efficient antioxidant activity within lipid peroxidation tests (Pietarinen et al 2006).…”
Section: Antifungal and Antibacterial Activitiesmentioning
confidence: 90%
“…En este sentido, la ICM es similar a la reportada por El-Kateeb et al (2013) con extractos metanólicos al 0.4 % de hojas de V. vinifera 'Thompson seedless' y 'Flame seedless' (entre 63 y 72 %). Particularmente, el modo de acción de los polifenoles contra B. cinerea no ha sido totalmente explicado, pero se ha sugerido que actúan sobre la membrana citoplasmática, produciendo cambios en su permeabilidad, ocasionando liberación del contenido celular, coagulación del material citoplasmático y desorganización de organelos y membrana celular, todo ello inhibe el desarrollo del micelio y evita su esporulación (Adrian y Jeandet, 2012;Minova et al, 2015). Por otro lado, se ha indicado que polifenoles del tipo ácido 3b-hydroxy-kaurenoico están involucrados con reducción en la germinación de B. cinerea .…”
Section: Fully Bilingualunclassified
“…In particular, the action mode of polyphenols against B. cinerea has not been fully explained, but it has been suggested that they act upon the cytoplasmic membrane and change its permeability causing the cell content to be released, the cytoplasmic material to coagulate and the organelles and cell membrane to become disorganized. All this inhibits the development of mycelium and prevents sporulation (Adrian y Jeandet, 2012;Minova et al, 2015). It has been suggested that polyphenols of the type 3b-hydroxy-kaurenoic acid are involved in the reduction of B. cinerea spores germination .…”
Section: Fully Bilingualmentioning
confidence: 99%
“…On the other side, removed bark represents row material with a whole scale of valuable purposes. Substrate formulations, soil conditioners, plant protection, health and industrial products, bioremediation agents are some of the potential applications of this material considered as a waste [1,[3][4][5][6]. Coniferous bark as a component of commercial substrates increases water and nutrient availability and exhibits antifungal, antibacterial, and insecticidal effects [3][4].…”
Section: Introductionmentioning
confidence: 99%